TakeTwo: an indexing algorithm suited to still images with known crystal parameters. Issue 8 (4th August 2016) - Ginn, Helen Mary; Roedig, Philip; Kuo, Anling; Evans, Gwyndaf; Sauter, Nicholas K.; Ernst, Oliver; Meents, Alke; Mueller-Werkmeister, Henrike; Miller, R. J. Dwayne; Stuart, David Ian
Abstract : A novel indexing method is presented that is well suited to the minimal information on a still image diffraction pattern and can achieve indexing rates of over one lattice per image. Abstract : The indexing methods currently used for serial femtosecond crystallography were originally developed for experiments in which crystals are rotated in the X‐ray beam, providing significant three‐dimensional information. On the other hand, shots from both X‐ray free‐electron lasers and serial synchrotron crystallography experiments are still images, in which the few three‐dimensional data available arise only from the curvature of the Ewald sphere. Traditional synchrotron crystallography methods are thus less well suited to still image data processing. Here, a new indexing method is presented with the aim of maximizing information use from a still image given the known unit‐cell dimensions and space group. Efficacy for cubic, hexagonal and orthorhombic space groups is shown, and for those showing some evidence of diffraction the indexing rate ranged from 90% (hexagonal space group) to 151% (cubic space group). Here, the indexing rate refers to the number of lattices indexed per image.